SPECIES COMPOSITION OF PSAMMOPHILIC CILIATES OF SUMGAIT CASPIAN COAST - I. Kh. Alekperov; A. Agaeva (Юг России: экология, развитие, 2014)
Abstract. Comparative data on the species composition and species saprobic indicators of the psammon ciliates from Sumgait coast of the Caspian Sea are given.Methods. “Alive” samples were collected using a small clean plastic wide mouth bottles. Further processing was carried out under laboratory conditions. Small quantities of soil were examined under a binocular microscope MBS-9 . Ciliates detected microvessel caught and fixed castors for further impregnation kinetoma silver nitrate (Chatton et Lwoff, 1930) or silver proteinate. To determine the keys for ciliates used Foyssner’s major publications (Foissner et al., 1991, 1992, 1999) and “Free-living ciliates Atlas” (Alekperov, 2005).Results. We observed 75 species of ciliates during the studies, which species composition and distribution of the collection points are shown in table 1. Diagrams with average data were made relations groups psammophilous ciliates indicators saprobity different zones for each of the sites investigated Sumgait coast.Main conclusions. Environmental analysis using benthic ciliates indicators saprobity different zones showed that as expected, the industrial zone of Sumgayit coast coast, despite the decline in recent years, the total amount of pollution that is still highly contaminated portion of the coastal zone of the Caspian Sea.